Elimination of the flavodiiron electron sink facilitates long-term H2 photoproduction in green algae - Martina Jokel; Valéria Nagy; Szilvia Z. Tóth; Sergey Kosourov; Yagut Allahverdiyeva (BioMed Central, 2022)
Background
The development of renewable and sustainable biofuels to cover the future energy demand is one of the most challenging issues of our time. Biohydrogen, produced by photosynthetic microorganisms, has the potential to become a green biofuel and energy carrier for the future sustainable world, since it provides energy without CO2 emission. The recent development of two alternative protocols to induce hydrogen photoproduction in green algae enables the function of the O2-sensitive [FeFe]-hydrogenases, located at the acceptor side of photosystem I, to produce H2 for several days. These protocols prevent carbon fixation and redirect electrons toward H2 production. In the present work, we employed these protocols to a knockout Chlamydomonas reinhardtii mutant lacking flavodiiron proteins (FDPs), thus removing another possible electron competitor with H2 production.
Results
The deletion of the FDP electron sink resulted in the enhancement of H2 photoproduction relative to wild-type C. reinhardtii. Additionally, the lack of FDPs leads to a more effective obstruction of carbon fixation even under elongated light pulses.
Conclusions
We demonstrated that the rather simple adjustment of cultivation conditions together with genetic manipulation of alternative electron pathways of photosynthesis results in efficient re-routing of electrons toward H2 photoproduction. Furthermore, the introduction of a short recovery phase by regular switching from H2 photoproduction to biomass accumulation phase allows to maintain cell fitness and use photosynthetic cells as long-term H2-producing biocatalysts.